The Job Interview and Cognitive Performance: Does Structure Reduce Performance on Selection Batteries, and Can Explanation of Purpose Improve It?. Issue 2 (1st July 2016) - Bragger, Jennifer; Kutcher, Eugene J.; Schettino, Gaynell; Muzyczyn, Bridget; Farago, Pamela; Fritzky, Emily
Abstract : Structuring job interviews is a method of decreasing bias and increasing the predictive validity of job performance, but research suggests that applicants can react negatively to structure (Chapman & Zweig, 2005) and that negative attitudes about selection tools can predict performance (Hausknecht, Day, & Thomas, 2004). The current exploratory study investigates how structuring the job interview in conjunction with priming the ethnicity and sex of the applicant, and in some conditions providing an explanation of the structure, affected post‐interview cognitive ability performance. Three levels of structure were randomly assigned. Those who experienced a structured interview without an explanation of its purpose scored lower than those who experienced an unstructured interview, but those who experienced a structured interview with an explanation of its purpose did not score lower than those who experienced an unstructured interview. Scores differed for females and Hispanics depending on the structure condition, but not in the same manner. Implications for recruitment, selection, and performance management are discussed.